Role of the Sympathetic Nervous System and Its Modulation in Renal Hypertension - Sata, Yusuke; Head, Geoffrey A.; Denton, Kate; May, Clive N.; Schlaich, Markus P. (Frontiers in Medicine, 2018)
The kidneys are densely innervated with renal efferent and afferent nerves to communicate with the central nervous system. Major structural components of the kidneys such as blood vessels, tubules, the pelvis, and glomeruli form a bi-directional neural network to relay sensory and sympathetic signals to and from brain. Renal efferent nerves regulate renal blood flow, glomerular filtration rate, tubular reabsorption of sodium and water, as well as release of renin and prostaglandins, all of which contribute to cardiovascular and renal regulation. Renal afferent nerves complete the feedback loop with signals integrated in the brain stem modulating central sympathetic outflow and both types of nerves form integral parts of the self-regulated reno-renal reflex loop. Renal sympathetic nervous system activity is commonly increased in pathophysiological conditions such as hypertension and chronic- and end-stage renal disease. Increased renal sympathetic nervous system activity raises blood pressure and can contribute to the deterioration of renal function Attempts have been made to eliminate or interfere with this important link between the brain stem and the kidneys as a neuromodulatory treatment for these conditions. Catheter-based renal sympathetic denervation has been successfully applied in patients with resistant hypertension and was associated with significant falls in blood pressure and renal protection in most studies performed. The focus of this review is the neural contribution to renal and cardiovascular hemodynamics and renal function in the setting of hypertension and chronic kidney disease as well as the specific roles of renal efferent and afferent nerves in this scenario and their utility as a therapeutic target.